Protagonismo juvenil : problematizando espaços de sociabilidade juvenil no contexto eclesial - Becker, Claudio Giovani (2007)
This study is intended to serve as an instrument for questioning about the church spaces used for juvenile socialization, aiming at promoting their protagonism, which results in the empowerment of young people. This research made use of the Freire dialogical process based on the educational practice developed within the youth groups of the church. Bibliographical research was also carried out on authors who work in this area granting a theoretical foundation for this work. In this exercise readings have been listed of young protagonists involved in the life experience and formative spheres with the intention of evaluating their space in the church, identifying their needs and how much these needs are tended to through the proposed work policies. It becomes evident that the young people are thirsting for a space of responsibility and visibility, which permits an integration into the whole of the church, passing from spectators to administrators of actions which results in the creation of referential ties of trust. These initiatives signal foundations for a possible ressignification of this traditional space of socialization.